Insights on the opening of the Galerian mammal migration pathway from magnetostratigraphy of the Pleistocene marine-continental transition in the Arda River section (northern Italy). Issue 2 (September 2016) - Monesi, Edoardo; Muttoni, Giovanni; Scardia, Giancarlo; Felletti, Fabrizio; Bona, Fabio; Sala, Benedetto; Tremolada, Fabrizio; Francou, Carlo; Raineri, Gianluca
Abstract: We investigated the magnetostratigraphy of the Arda River section (northern Italy) where the transition from marine to continental sedimentation occurring in the Po River basin during the Pleistocene is registered. Four magnetic polarity reversals were used to construct an age model of sedimentation aided by marine biostratigraphy and tied to a standard δ 18 O curve from the literature. The section spans from the Olduvai subchron (1.94-1.78 Ma) across the Jaramillo subchron (1.07-0.99 Ma) up to the Brunhes—Matuyama boundary (0.78 Ma). The onset of continental deposition occurred during marine isotope stage (MIS) 30 at ∼1.04 Ma. An association of Villafranchian and Early Galerian mammals, including Sus strozzii and Ursus dolinensis, has been found in the continental sediments dated to MIS 29-27 (∼0.99 Ma). Above follows a prominent fluvial conglomerate attributed to the first major low stand of the Pleistocene culminating with MIS 22 at ∼0.9 Ma during the late Early Pleistocene climate turnover (EPT). These and other data from the literature are used to reconstruct the onset of continental deposition in the greater Po basin and shed light on the opening of the migration pathway that brought far-traveled Galerian mammal immigrants to enter Europe for the first time during the EPT.